A dangerous legacy : Judaism and the psychoanalytic movement - Reijzer, H. M. (Karnac History of Psychoanalysis Ser., 2011)
On 23rd July 1908 Sigmund Freud wrote to his colleague Karl Abraham: "Rest assured that if my name were Oberhuber [an obviously non-Jewish name], in spite of everything my innovations would have met with far less resistance."From its beginning, psychoanalysis has been seen as a Jewish affair, and psychoanalysts have always been afraid of ending up in the position of the Jew - that of the outsider. In A Dangerous Legacy: Judaism and Psychoanalysis Hans Reijzer examines how psychoanalysts have managed that fear, in the recent past and in the present. During his research, which led him to Vienna